Sugar Metabolism Regulates Flavor Preferences and Portal Glucose Sensing - Zhang, Lingli; Han, Wenfei; Lin, Chenguanlu; Li, Fei; de Araujo, Ivan E. (Frontiers in Integrative Neuroscience, 2018)
In most species, including humans, food preference is primarily controlled by nutrient value. In particular, glucose-containing sugars exert exquisitely strong effects on food choice via gut-generated signals. However, the identity of the visceral signals underlying glucose’s rewarding effects remains uncertain. In particular, it is unknown whether sugar metabolism mediates the formation of preferences for glucose-containing sugars. Using the mouse as a model organism, we made use of a combination of conditioning schedules, gastrointestinal nutrient administration, and chromatographic/electrochemical methods to assess the behavioral and neural effects of activating the gut with either metabolizable glucose or a non-metabolizable glucose analogue. We show that mice display much superior preferences for flavors associated with intra-gastric infusions of glucose compared to flavors associated with intra-gastric infusions of the non-metabolizable glucose analogue α-methyl-D-glucopyranoside (“MDG”, an activator of intestinal sodium/glucose cotransporters). These effects were unaffected by surgical bypassing of the duodenum, suggesting glucose-specific post-absorptive sensing mechanisms. Consistently, intra-portal infusions of glucose, but not of MDG, induced significant rises in dopamine levels within brain reward circuits. Our data reveal that the unmatched rewarding effects of glucose-containing sugars cannot be accounted for by metabolism-independent activation of sodium/glucose cotransporters; rather, they point to glucose metabolism as the physiological mechanism underlying the potent reward value of sugar-sweetened flavored beverages. In particular, no circulating “gut factors” need to be invoked to explain the reward value of ingested glucose. Instead, they suggest that portal-mesenteric sensing of metabolizable glucose as the preferential physiological pathway for sugar reward.